Ketogenic diet: a potential adjunctive treatment for substance use disorders - Kong, Deshenyue; Sun, Jia-xue; Yang, Ji-qun; Li, Yuan-sen; Bi, Ke; Zhang, Zun-yue; Wang, Kun-hua; Luo, Hua-you; Zhu, Mei; Xu, Yu (Frontiers in Nutrition, 2023)
Substance use disorders (SUD) can lead to serious health problems, and there is a great interest in developing new treatment methods to alleviate the impact of substance abuse. In recent years, the ketogenic diet (KD) has shown therapeutic benefits as a dietary therapy in a variety of neurological disorders. Recent studies suggest that KD can compensate for the glucose metabolism disorders caused by alcohol use disorder by increasing ketone metabolism, thereby reducing withdrawal symptoms and indicating the therapeutic potential of KD in SUD. Additionally, SUD often accompanies increased sugar intake, involving neural circuits and altered neuroplasticity similar to substance addiction, which may induce cross-sensitization and increased use of other abused substances. Reducing carbohydrate intake through KD may have a positive effect on this. Finally, SUD is often associated with mitochondrial damage, oxidative stress, inflammation, glia dysfunction, and gut microbial disorders, while KD may potentially reverse these abnormalities and serve a therapeutic role. Although there is much indirect evidence that KD has a positive effect on SUD, the small number of relevant studies and the fact that KD leads to side effects such as metabolic abnormalities, increased risk of malnutrition and gastrointestinal symptoms have led to the limitation of KD in the treatment of SUD. Here, we described the organismal disorders caused by SUD and the possible positive effects of KD, aiming to provide potential therapeutic directions for SUD.